The H.E.R.B.A.L guide : dietary supplement resources for the clinician - Bonakdar, Robert Alan (Wolters Kluwer Health/Lippincott William & Wilkins, 2010)
Assists clinicians in counseling patients about use of herbal and dietary supplements and integrating these supplements into the comprehensive clinical management of common conditions. This title offers practical advice on the clinician-patient dialogue about supplements. It discusses key issues regarding labeling, dosing, and regulation